Effects of Cardiac Telerehabilitation During COVID-19 on Cardiorespiratory Capacities in Patients With Coronary Artery Disease - Fanget, Marie; Bayle, Manon; Labeix, Pierre; Roche, Frédéric; Hupin, David (Frontiers in Physiology, 2022)
Background The COVID-19 pandemic led to the closure of most cardiac therapy centers. One of the solutions was to adapt the existing cardiac rehabilitation (CR) program in an institute to a remote approach offered by home-based telerehabilitation. The aim of this study was to measure the cardiorespiratory effects of telerehabilitation compared to conventional center-based CR. Methods Patients were assigned to two 3-week CR programs: telerehabilitation and conventional center-based CR. The telerehabilitation group wore a connected watch to monitor heart rate (HR) and gave their perception of effort according to a modified Borg scale. The exercise training (4 sessions/week) consisted of 1-h aerobic endurance and strength training session at the target HR zone determined by results based on cardiopulmonary exercise test (CPET) and perception of effort, respectively. The exercise protocol was the same for conventional CR participants except the duration of session that lasted 2 h instead of one. The weeks before and after the training program, peak oxygen uptake (VO2 peak), oxygen uptake at first ventilatory threshold (VO2 at VT1), peak workload, percent of predicted maximum HR, and the absolute differences in HR and systolic blood pressure between maximum and recovery at 1 min and 3 min were measured using a CPET. A two-way ANOVA with one repeated measure and one independent factor was performed. Results 54 patients (mean age: 61.5 ± 8.6 y, 10 women) equally split in the two groups were included in this experiment. A significant increase was observed in both groups on VO2 peak (telerehabilitation: 8.1 ± 7.8 % vs. conventional: 10.1 ± 9.7 %, p<0.001), VO2 at VT1 (telerehabilitation: 8.8 ± 4.4 % vs. conventional: 7.3 ± 19.0 %, p=0.02) and peak workload (telerehabilitation: 16.6 ± 18.9 % vs. conventional: 17.2 ± 7.0 %, p<0.001) after the 3-week telerehabilitation and conventional CR, respectively. No significant difference was noticed between both groups. Conclusion A 3-week exercise program improved patients’ cardiorespiratory fitness. Telerehabilitation was as effective and represents a safe alternative CR program during the COVID-19 period. In the future, this approach could facilitate the continuity of care for patients unable to participate in center-based CR.